Pengembangan Aplikasi Interaksi Masyarakat Terpadu Kota Malang Berbasis Geotagging dan Social Crowdsource - Igar Ramaddhan; Herman Tolle; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Submitting complaints and aspirations from the community to the city government is one form of community interaction problem with the government. This problem arises because of the high rate of population growth in a city. Apart from social problems and government bureaucracy, 201 natural disasters were recorded as having occurred in 2019 in Malang City. So far, disaster notification and reporting services or systems have not been developed in Malang City. Notifications are still delivered via social media accounts such as government Twitter accounts. Various complaints compliant applications such as Sambat Online have been created to improve the comfort of the people of Malang City, but no application collects complaints and disaster information based on social crowdsourcing. This research will discuss and develop solutions to the problem of centralization of information for the delivery of complaints and disasters from the community. This study uses the Scrum development method. This method was chosen because the system requirements can change over time. The system is developed using the Firebase platform as a data storage area and the Flutter framework with the Dart programming language as its interface. It is hoped that the system can make the community life of Malang City residents more comfortable, with the results of the usability testing score is 85.5 which means it is acceptable, then the validation test results are satisfactory with all valid test results, and compatibility testing with the results of the system can run on Android 5.1 to above and iOS 12.4 and above.